2019
DOI: 10.1187/cbe.18-06-0103
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Holistic Review in Graduate Admissions That Decouples the GRE from Race, Ethnicity, and Gender

Abstract: Graduate schools around the United States are working to improve access to science, technology, engineering, and mathematics (STEM) in a manner that reflects local and national demographics. The admissions process has been the focus of examination, as it is a potential bottleneck for entry into STEM. Standardized tests are widely used as part of the decision-making process; thus, we examined the Graduate Record Examination (GRE) in two models of applicant review: metrics-based applicant review and holistic app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 23 publications
(35 reference statements)
1
45
0
Order By: Relevance
“…Many graduate programs have already removed the GRE requirement or are considering making it optional, and the pandemic may accelerate this trend. [9][10][11][12] The long-term implications of dropping the GRE requirement will need to be assessed to determine whether this metric measures important qualities and if the GRE predict graduate student outcomes.…”
Section: Admissions and Program Onboardingmentioning
confidence: 99%
“…Many graduate programs have already removed the GRE requirement or are considering making it optional, and the pandemic may accelerate this trend. [9][10][11][12] The long-term implications of dropping the GRE requirement will need to be assessed to determine whether this metric measures important qualities and if the GRE predict graduate student outcomes.…”
Section: Admissions and Program Onboardingmentioning
confidence: 99%
“…Studies have shown the problematic use of Physics GRE scores due to a performance bias against women and underrepresented minorities [6][7][8]. At the same time, incorporating holistic review for STEM graduate admissions allows for such quantitative measures to still be utilized, while reducing risk of racial/ethnic and gender bias by having GRE scores (general and subject-test) as just one element within a broad holistic graduate application [9,10]. However, much of the literature on the use of Physics GREs in graduate admissions has been focused exclusively on the faculty and programmatic side of this equation with student voices remaining largely absent.…”
Section: Introductionmentioning
confidence: 99%
“…The GRE ranked as important or most important during screenings by 33% of the programs. We suggest that is problematic because using the GRE for metrics-based review of applicants has been found to exclude twice the number of applicants who identify as a historically URM compared with their peers (Wilson et al, 2019). However, holistic admission strategies mitigate this exclusion.…”
Section: Discussionmentioning
confidence: 99%